Understanding peaceful and violent nation-building through leadership : a case study of South Sudan - Schoeman, Maxi (University of Pretoria, 2018)
Peace-building has reached a cross-roads. The high instance of conflict relapse in “post-conflict” societies has stimulated an examination of dominant peace-building thinking and practice. This research contributes to this thinking by examining nation-building in societies plagued by identity-related conflicts, specifically in South Sudan. It does so using the leadership process approach. The question driving this enquiry is to discover whether the leadership process approach can shed light on why South Sudan failed to build a nation that sustains peace. By using the leadership process approach, this study contributes to a better understanding of nation-building and how it contributes to both conflict and peace processes, allowing for a greater understanding of the relationship between nation-building and peace-building and why dominant state-building approaches to peace-building are incomplete. Using existing literature, the thesis provides a cohesive conceptual framework of the nation combining five elements: a national identity, link to a territory, a claim to political organisation and self-government, collective will and collective responsibility. This provides the key themes and indicators which are examined using the leadership process approach. The leadership process approach, which conceptualises leadership as a relationship between leaders, followers and situations, provides the analytical tools that are used to explain the emergence of the five elements of the conceptual framework of the nation. These tools include an examination of the leader-follower relationship based on mutuality and the exchange of influence, situational leadership and the sources of power. This framework is used to understand South Sudan. A case study approach is used to ensure a full examination of the relationship between nation-building and peace-building using the leadership process. Multiple forms of data collection were used including documentary analysis, a literature review and interviews. This data is analysed using the process tracing approach. The analysis includes South Sudan’s early history through to the signing of the most recent peace agreement in 2015. South Sudan’s early history of conquest and colonisation, the first Sudanese civil war, the second Sudanese civil war and the current South Sudanese civil war are all explored in depth. The study finds that the leadership process approach allows for a more nuanced and holistic understanding of the South Sudanese conflict specifically and nation-building in general. It shows that peace-building failed in South Sudan because of the conflict-reinforcing nature of the nation-building and leadership processes that have been replicated at national, regional and local levels. It concludes with several lessons learned for both nation-building and peace-building.